Development of smart materials with versatile bending capabilities using microcellular foaming process: influence of foaming and desorption time - Lim, Donghwan; Kim, Jaehoo; Hong, Jin; Kim, Kwanhoon; Cha, Sung Woon (Institute of Physics Publishing, 2024)
Herein, a smart material with versatile bending capability is developed using a microcellular foaming process (MCPs). In contrast to previous hydrogel-based approaches, the bi-layered smart material is fabricated using typical thermoplastics, polyethylene terephthalate glycol (PETG) and polymethyl methacrylate (PMMA), to achieve shape deformation in response to thermal stimuli. Further, the theoretical model for bi-layered smart materials based on the modified Timoshenko's model is employed to predict and comprehend this thermal response phenomenon. Due to the distinct foaming characteristics of the two polymers, a reversal in the bending direction is achieved by manipulating the foaming and desorption time. The length variation after foaming differs depending on the desorption time for each polymer. PMMA decreases in length after foaming, measuring 56.25 mm at a desorption time of 40 min and 53.16 mm at 80 min. On the other hand, PETG shows an increase in length after foaming, measuring 53.33 mm at 40 min and 58.25 mm at 80 min. Consequently, when the two polymers are bonded and foamed, bending occurs depending on the desorption time, and a reversal in the bending direction is observed at the critical desorption time of around 60 min. Based on this result, the folding direction of a five-leafed flower-shaped object is successfully altered under thermal stimuli. This innovative approach extends the category of smart materials beyond the hydrogels and showcases the potential of the MCPs for the creation of smart materials for various applications that require versatile shape changes in response to temperature.